Personnel Economics: Past Lessons and Future Directions Presidential Address to the Society of Labor Economists, San Francisco, May 1, 1998 - Lazear, Edward P. (Journal of Labor Economics, 1999)
In 1987, the Journal of Labor Economics published an issue on the economics of personnel. Since then, personnel economics, defined as the application of labor economics principles to business issues, has become a major part of labor economics, now accounting for a substantial proportion of papers in this and other journals. Much of the work in personnel economics has been theoretical, in large part because the data needed to test these theories have not been available. In recent years, a number of firm‐based data sets have surfaced that allow personnel economics to be tested. Using two such data sets, I give support to the implications of theories that relate to life‐cycle incentives, tournaments, piecework incentives, pay compression, and peer pressure. I conclude that personnel economics is real. It is far more than a set of clever theories. It has relevance to the real world. Additionally, firm‐based data make asking and answering new kinds of questions feasible. The value of research in this area is high because so little is known compared with other fields in labor economics. Questions about the importance of a worker's relative position in a firm, about intrafirm mobility, about the effect of the firm's business environment on worker welfare, and about the significance of first impressions can be answered using the new data. Finally, I argue that the importance of personnel economics in undergraduate as well as business school curricula will continue to grow.